Missing Dimensions in Contemporary Islamic Movements - Taha J. al 'Alwani (International Institute of Islamic Thought, 1995)
Opening Remarks This paper will examine dimensions that seem to be absent, whether totally or partially, from the thought and practice of certain contemporary Islamic movements in the Muslim world, many of which may be viewed as extensions of the liberation movements that played significant roles in maintaining the ummah's identity at the tum of the twentieth century. We will address these movements and remind them, for "remembrance does the faithful a world of good" and "wisdom is the pursuit of the faithful; wherever it is found it should be cherished." Since God created Adam, people have fallen into two categories: those who perform their roles according to the teachings of revelation and those whose roles originate from their own ideas, desires, and views or those that have been passed down from their ancestors. The first type sees history as the outcome of conflict between humanity and nature. In response to the latter, the true religion-Islam-has been the indispensable sine qua non for correcting humanity's basic assumptions, rebuilding its vision, helping it to find peace of mind, and providing it with answers to quintessential quesions. The use of Islam as the foundation for both thought and practice is the force that drives activist Muslims. In the Qur'an, God revealed a perfect text that responds to questions of existence at all levels.1 Moreover, God has linked the Qur'an's totality and all-encompassing explanatory nature to the responsibility of witnessing that, after the Prophet, was passed on to the ummah.2 Through the testimony of the Prophet and of the ummah, God will certainly cause His purposes to prevail.3 We define this witnessing as a consciously responsible type of witnessing that has its own economic, social, and intellectual characteristics based on a specific societal order, on the one hand, and a specific scientific and methodological order on the other. Our responsibility in witnessing, then, is much greater than we have envisaged or put into practice in the past. Certain dimensions that are absent from our perspectives and practices may be uncovered by weighing them against the objectives manifest in the repsonsibility of witnessing.4 This process makes the issue of reform and change a composite, as opposed to a simple, one. Moreover, both factors require an awareness that must be "methodological" and that examines all dimensions at the levels of both theory and application. In this way, we may gain an understanding of the agents that affect change and generate deviation and the resulting crises ...